2021
DOI: 10.1038/s41598-021-01693-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system lymphomas express immunohistochemical factors of autophagy

Abstract: Primary central nervous system lymphoma (PCNSL) is an aggressive and rare disease. Autophagy is a catabolic mechanism boosting various tumors, including lymphomas; its inhibition is thus a promising therapeutic target. Its presence has never been studied in PCNSLs. We conducted a retrospective immunohistochemical study of 25 PCNSLs for LC3B, p62, and M6PR, comparing it with clinicopathological characteristics. Fourteen (56%) and eleven (44%) PCNSLs were of low and high LC3B expression, respectively. p62 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Many studies have suggested the role and significance of autophagy in the development of systemic lymphoma [ 47 , 48 ]. However, only 1 research has provided evidence for the possible existence of autophagy markers in PCNSLs, but has not mentioned the correlation with PI3K/AKT/mTOR signaling pathway [ 49 ]. Further investigation is needed to explore this promising issue.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested the role and significance of autophagy in the development of systemic lymphoma [ 47 , 48 ]. However, only 1 research has provided evidence for the possible existence of autophagy markers in PCNSLs, but has not mentioned the correlation with PI3K/AKT/mTOR signaling pathway [ 49 ]. Further investigation is needed to explore this promising issue.…”
Section: Discussionmentioning
confidence: 99%